Osteosarcoma Cell-Derived Small Extracellular Vesicles Enhance Osteoclastogenesis and Bone Resorption Through Transferring MicroRNA-19a-3p - Luo, Tingting; Zhou, Xiaocheng; Jiang, Erhui; Wang, Lin; Ji, Yaoting; Shang, Zhengjun (Frontiers in Oncology, 2021)
Osteosarcoma (OS) is the most common primary bone cancer characterized by an aggressive phenotype with bone destruction. The prognosis of OS patients remains unoptimistic with the current treatment strategy. Recently, osteoclasts are believed to play a crucial role in cancer bone metastasis. Thus, osteoclast could be a target both in bone destruction and cancer progression in OS. However, mechanisms governing osteoclastogenesis in OS remain poorly understood. miRNA delivered by small extracellular vesicles (sEVs) could mediate cellular communications. In this study, we investigated the effects of sEVs on osteoclastogenesis and osteoclast function, also clarified the underlying mechanism. We herein found that sEVs promoted pre-osteoclast migration, osteoclastogenesis and resorption by exposing RAW264.7 cells to sEVs derived from OS cells. Bioinformatics analysis showed that phosphatase tension homologue (PTEN), and miR-19a-3p were involved in OS progression. Overexpression of miR-19a-3p or sEVs’ miR-19a-3p promoted osteoclast formation and function through PTEN/PI3K/AKT signaling pathway, while inhibition of miR-19a-3p showed the contrary results. The bone marrow macrophages (BMMs) were used to verify the results. OS mice which were established by subcutaneous injection of OS cells exhibited increased levels of sEVs’ miR-19a-3p in blood. Moreover, micro-computed tomography (CT) and histomorphometry analysis demonstrated that OS mice exhibited osteopenia with increased number of osteoclasts. In conclusion, miR-19a-3p delivery via OS cell-derived sEVs promotes osteoclast differentiation and bone destruction through PTEN/phosphatidylinositol 3 -kinase (PI3K)/protein kinase B (AKT) signaling pathway. These findings highlight sEVs packaging of miR-19a-3p as a potential target for prevention and treatment of bone destruction and cancer progression in OS patients. And this finding provides a novel potentially therapeutic target for the bone metastasis.